Pengaruh Pemahaman Knowledge Sharing terhadap Prestasi Mahasiswa yang Melaksanakan Praktek Pengalaman Lapangan (Studi pada Mahasiswa STKIP Nasional Padang Pariaman) - Sumarni Sumarni (Universitas Batanghari Jambi, 2020)
The purpose of this study is to analyze the understanding of knowledge sharing on the achievements of students who carry out field experience. This research uses quantitative research methods with the research design used is descriptive research. The population was 176 students using a non probability sampling technique, so the sample of 64 students was calculated using the Slovin formula. Data analysis techniques used in this study were descriptive statistics, classic assumption tests and linear regression analysis with the help of a computer program version 23. The results of this study use the t test, where knowladge sharing (X) has a positive value direction of 4.035 which has a value greater than t table of 1,671 with a significance value of 0,000 <0.05 which means that it has a significant effect. So it can be concluded that the understanding of knowledge sharing (X) affects the achievement of students who carry out field experience.